The influence of nursing home managers' leadership on person-centred care and stress of conscience: A cross-sectional study - Annica Backman; Karin Sjögren; Hugo Lövheim; Marie Lindkvist; David Edvardsson (BMC, 2021)
Abstract Background Leadership and stress are common concepts in nursing, and this study explores empirically the connection between leadership and stress of conscience in the context of aged care practice. Previous literature has shown that when staff are unable to carry out their ethical liabilities towards the residents, feelings of guilt may occur among staff, which may be an expression of stress of conscience. Although leadership has been described as crucial for staff's work perceptions of stress as well as for person-centred practices, the influence of nursing home managers' leadership on stress of conscience among staff and person-centred practices is still not fully explored. This study attempts to address that knowledge gap by exploring the relationship between leadership, person-centred care, and stress of conscience. Methods This study was based on a cross-sectional national survey of 2985 staff and their managers in 190 nursing homes throughout Sweden. Descriptive statistics and regression modelling were used to explore associations. Results Leadership was associated with a higher degree of person-centred care and less stress of conscience. A higher degree of person-centred care was also associated with less stress of conscience. The results also showed that leadership as well as person-centred care were individually associated with lower levels of stress of conscience when adjusting for potential confounders. Conclusion Nursing home managers' leadership was significantly associated with less staff stress of conscience and more person-centred care. This indicates that a leadership most prominently characterised by coaching and giving feedback, relying on staff and handling conflicts constructively, experimenting with new ideas, and controlling work individually can contribute to less staff stress as well as higher degree of person-centred care provision.